Jobs for the boys? The employment experiences of secondary school-leavers in Zimbabwe. - Bennel, Paul; Ncube, Mkhuhuli (Journal of Southern African Studies)
Discusses the main results of a comprehensive tracer survey of Form IV school-leavers from urban and rural secondary schools in Zimbabwe during the mid-to-late 1980s. Wage employment; Occupational profiles and preferences; Self-employment; Unemployment.